Essential University Physics: Volume 1 (3rd Edition)

Published by Pearson
ISBN 10: 0321993721
ISBN 13: 978-0-32199-372-4

Chapter 7 - Exercises and Problems - Page 126: 41


Please see the work below.

Work Step by Step

We know that $K_U=K_{\circ}+U_{\circ}$ $\implies (\frac{1}{2})mv^2+0.0=(\frac{1}{2})mv_{\circ}^2+mgh$ $\frac{1}{2}mv^2=\frac{1}{2}mv_{\circ}^2+mgh$ $\frac{1}{2}v^2=\frac{1}{2}v_{\circ}^2+gh$ $v^2=v_{\circ}^2+2gh$ $v=\sqrt{v_{\circ}^2+2gh}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.